Impact of public expenditures on FDI inflows into developing countries - Othman, Norashida; Andaman, Gul; Yusop, Zulkornain; Ismail, Mohd Mansor (Universiti Putra Malaysia Press, 2018)
This paper uses Pesaran et al.'s (1999) Pooled Means Group (PMG) estimation to explore the role of government expenditures of the host countries on Foreign Direct Investment (FDI) inflows. The PMG estimator allows for a greater degree of parameter heterogeneity by imposing common long-run relationships across countries. A panel data from 24 developing countries was utilised for the study period between 1982 and 2014. The empirical results show government expenditure significantly promotes FDI inflows in the long-term. The results also suggest that market size plays an important role in FDI inflows.